Bentuk Komunikasi Pendidikan Karakter Mahasiswa Vokasi Bidang Perkebunan Terhadap Pembentukan Karakter Iman Dan Takwa - M. Atta Bary; Herijanto Thamrin; Supriansyah Supriansyah (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Everyone's personality is a very complex part, including the values that are believed, the attitudes taken, the behaviors shown, and the morals adhered to. Each individual student has a personality that reflects the nature and how students interact within their social community. This phase is very important in the formation of student character, in this condition the outlook on life and life values as a dynamic and mature human being is awakened, students begin to build the foundation of their personality. The purpose of this research is to form the character of faith and piety for vocational students in the field of plantations to build a superior personality. The research method is qualitative with a qualitative-phenomenological approach. The subject of this activity is vocational college students who are determined by purposive sampling. The object of the research is students with their daily drivers in the form of gadgets. Data was collected through observation, interviews, and documentation. Furthermore, the data was analyzed with the Miles and Huberman interactive model. The results of this activity are in the form of an important role in adding elements of religious values for students as the main foundation of national values and parameters of religious norms that synergize and are introduced in every lecture to produce Muslim students who are pioneers of change and overcome the problems of the state and nation.